Review on Recent Advances in Titanium Dye Oxide Nanoparticles for Dye Sensitized Solar Cell Applications - divya Chandran (International Journal of Advances in Applied Sciences, 2017)
Alternate energy source becomes a crucial for green energy solution against ever increasing demand. Dye Sensitized solar cell is another promising option toward green energy providing opportunity to explore natural dye extracts from plants. This review explores recent developments in the field of Dye Sensitized solar cell technology specifically with sensitizer synthesized from plants which are also found in India. Anthocyanin, betalain, chlorophyll and carotenoids are among the most common plant pigments explored as sensitizers. The review of different attempts on fabrication of natural dye based solar cells implies that titanium dioxide (TiO2) nano particles can be used as photoanode, platinum (Pt) as counter electrode and iodine/iodide electrolyte. Plant pigments are highly pH sensitive and can alter solar cell performance based on its extraction method, concentration and its ability to anchor with photoanode. Stability of dye, absorption in near IR range and leakage of liquid electrolyte are few of the challenges ahead. However, natural dye is biodegradable and non-toxic having most of the extraction process harmless to environment. In addition, natural dye has the promising future as it is abundant.